Replication and Immunogenicity of Swine, Equine, and Avian H3 Subtype Influenza Viruses in Mice and Ferrets - Baz, Mariana (American Society for Microbiology, 2013)
Since it is difficult to predict which influenza virus subtype will cause an influenza pandemic, it is important to prepare influenza virus vaccines against different subtypes and evaluate the safety and immunogenicity of candidate vaccines in preclinical and clinical studies prior to a pandemic. In addition to infecting humans, H3 influenza viruses commonly infect pigs, horses, and avian species. We selected 11 swine, equine, and avian H3 influenza viruses and evaluated their kinetics of replication and ability to induce a broadly cross-reactive antibody response in mice and ferrets. The swine and equine viruses replicated well in the upper respiratory tract of mice. With the exception of one avian virus that replicated poorly in the lower respiratory tract, all of the viruses replicated in mouse lungs. In ferrets, all of the viruses replicated well in the upper respiratory tract, but the equine viruses replicated poorly in the lungs. Extrapulmonary spread was not observed in either mice or ferrets. No single virus elicited antibodies that cross-reacted with viruses from all three animal sources. Avian and equine H3 viruses elicited broadly cross-reactive antibodies against heterologous viruses isolated from the same or other species, but the swine viruses did not. We selected an equine and an avian H3 influenza virus for further development as vaccines.